The delivery of regional anaesthesia for surgery - Jlala, Hatem A. (2010)
I have addressed in this thesis several major areas impacting upon the practice of regional anaesthesia in clinical practice. These include patient-centred issues (consent, anxiety and satisfaction) and technical issues affecting the delivery of service (needling and the use of ultrasound-guidance). While disparate, these issues combine to affect the efficient, safe and humane delivery of an important part of modern healthcare. These areas have been chosen as those most amenable to study and those with the greatest potential for real-world impact. Their unifying theme is the improvement in the delivery of regional anaesthesia.